MEDICALIZATION AND ITS HISTORY: STANDARDIZATION AND DISCIPLINATION OF CHILDREN THROUGH SCHOOL - Colombani, Fabiola [UNESP]; Castilho Caracio, Flavia Cristina; Maia Verissimo, Daniela Maria [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
The article aims to develop an essay about school medicalization and its history, with its emergence, and also about the school institution. Still, spend some thought on the bourgeois desire for morality and order with the medical influence on the family and school through medicalizing and biologizing practices of the learning process. From a literature review, we present and discuss the problem of medicalization as a practice that transforms school difficulties into medical issues, treating the biological body as an instrument of analysis and political advances with the purpose of extinguishing any undesirable behavior in the classroom. Finally, we associate the argumentative construction made here with the ideas of Adorno (1995), Adorno and Horkheimer (1986), Foucault (1979, 2008 a/b), Marques (1994), among others.
Keywords: Medicalization; School; Discipline; Standardization